POWER MEDIAN-BASED ESTIMATORS OF FINITE POPULATION MEAN - Yusuf, Ajibola Yahya; Audu, Ahmed; Yunusa, Mojeed Abiodun (FUDMA JOURNAL OF SCIENCES, 2024)
In this paper, median based mean estimators for estimating finite population mean are proposed. The proposed estimators were obtained by transforming estimators in literature utilizing mean of auxiliary variable into median based estimators with the aim of obtaining estimators with higher efficiency. The mean square error of the proposed estimators was obtained up to the first order of approximation using Taylor series approach and the optimum values of the unknown of the estimators were obtained by means of partial derivative of the mean square error and equating to zero. A Numerical study was carried out to support the fact that the proposed estimators are more efficient as compared to the existing ones, as the proposed estimators have the least mean squared error at optimum values of the unknown constants and have higher percentage relative efficiency (PRE). This implies that the proposed estimators are more efficient than the traditional ones considered in the study.
Keywords: Bias; Efficiency; Simple random sampling; Mean square error; Ratio estimator; Auxiliary information